African Tick Bite Fever Treated Successfully With Rifampin in a Patient With Doxycycline Intolerance. (13th May 2017) - Strand, Andrew; Paddock, Christopher D; Rinehart, Alex R; Condit, Marah E; Marus, Jessica R; Gillani, Shezeen; Chung, Ida H; Fowler, Vance G
Abstract: African tick bite fever is the most commonly encountered travel-associated rickettsiosis, occurring in as many as 5% of travelers returning from rural subequatorial Africa. This case report illustrates that rifampin represents an effective alternative to doxycycline for treatment of African tick bite fever in some selective situations.